Analisis Efektivitas Dan Efisiensi Anggaran Penanganan COVID-19 Kota Bandung - Naza Azella Ilma Agnia; Sri Mulyani; Indri Yuliafitri (CV. Multi Kreasi Media, 2026)
The implementation of the Covid-19 response budget in local governments faced several challenges, including limited health facilities, inappropriate planning, and budget refocusing policies. This study aims to analyze the effectiveness and efficiency of regional budget implementation and Covid-19 response programs in Bandung City. This research uses a qualitative method with interviews, documentation, and literature study. Informants consisted of 16 civil servants from the Bandung City Health Office. The results indicate that the implementation of the Covid-19 response budget was relatively effective, although the effectiveness rate declined in 2022. In terms of efficiency, the budget implementation was generally efficient, particularly in vaccination and testing programs, but not fully optimal due to the high use of resources compared to program achievements. Supporting factors include program alignment, government policies, and cross-sector assistance, while inhibiting factors include limited human resources, low community participation, and inadequate budget planning.